KESADARAN HUKUM BERLALU LINTAS PENGEMUDI ANGKUTAN KOTA TRAYEK KODE E DI MAKASSAR - Firman Muin; Santi Santi (Universitas Negeri Makassar, 2018)
This study aims: 1) To determine the legal awareness of traffic-route public transportation drivers in Makassar E code and 2) To determine the policing effort of the Republic Indinesia- Polwiltabes Makassar in raising legal awareness of traffic-route public transportation drivers in Makassar E code. To achieve these objectives, the researchers used a technique of collecting data through observation, interviews and documentation. Data have been obtained from the results of the study were processed using descriptive qualitative analysis to determine the legal awareness of traffic-route public transportation drivers in Makassar E code. The results showed that: 1) Awareness of the law-traffic public transportation drivers-stretch code E in Makassar still low measured based on legal knowledge, understanding of the law, the attitude of law and legal behavior that they did not know and did not understand the Act No. 22 of 2009 about traffic and road transport but they tend to know and understand the signs of traffic, but less appreciated and less obey the regulation, because it considers the breach as a habit, therefore it can be seen that the lack of legal awareness tends for violations so most The dominant influence of traffic law awareness of city transport drivers E in Makassar route code that behavior. 2) efforts to police the Republic Indinesia-Polwiltabes Makassar in raising awareness of traffic laws transport drivers in the city of Makassar, namely: a. preventive measures that, in order to tackle violations of traffic in the city of Makassar party Satlantas Polrestabes Makassar prevention efforts by conducting patrol-routine patrol / oprasi routine, held a raid of a motor vehicle and implement programs for improving knowledge of traffic in the form of activities: police friend to children , socialization cross-university / go to campus police, road safety, traffic safety campaign, the formation of traffic-related organizations as well as the automotive, KTL (Region traffic Code), driving schools, and others. And b.Upaya Tilang repressive ie, if follow-heavy offense, causing an accident, it can also be given sanctions in the form of imprisonment in accordance with Law No. 22 of 2009 on traffic and road transport.